Sector-specific productivity shocks in a matching model - Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2010)
Endogenous separation matching models have the shortcoming that they are barely able to replicate the Beveridge curve (i.e. the negative correlation between unemployment and vacancies) and business cycle statistics jointly. This paper builds upon the sectoral shock literature and combines its insights with the standard endogenous separation matching approach. We show that sectoral shocks can generate an aggregate Beveridge curve and perform reasonably well in explaining business cycle facts, especially compared to the one-sector baseline model.
Older version: http://hdl.handle.net/10419/30054
Keywords: E24; E32; J64; 330; Beveridge Curve; Endogenous Separations; Sectoral Productivity Shock; Beveridge-Kurve; Produktivität; Schock; Branche; Neoklassische Synthese; Matching; Zeitökonomie; Qualifikation; Allokation; Theorie